Modification of NiCoCrAlY with Pt: Part I. Effect of Pt depositing location and cyclic oxidation performance. Issue 3 (March 2019) - Yang, Yingfei; Yao, Hongrui; Bao, Zebin; Ren, Pan; Li, Wei
Abstract: Pt layers of 5 μm in thickness were electroplated before or after depositing NiCoCrAlY coating by arc ion plating (AIP) aiming for identifying the effect of Pt enriching position on microstructure and cyclic oxidation behavior of Pt modified NiCoCrAlY coatings. Al-rich zones formed at the same position of Pt-rich zones for both modified coatings due to uphill diffusion of Al driven by Pt. Cyclic oxidation tests at 1000 and 1100 °C indicated that oxidation resistance of NiCoCrAlY was improved by Pt modification via different mechanisms: at surface, Pt-rich zone promoted selective oxidation of Al to form α-Al2 O3, whilst at coating/substrate interface Pt-rich zone acted as effective diffusion barrier for titanium. Roles of Pt played in enhancing the oxidation performance of various Pt-modified NiCoCrAlY coating were investigated.